Phenology and seed germination behaviours of some wetland macrophytes at Biratnagar, Nepal - Niroula, Bhabindra; Panta, Praju (Nepalese Journal of Biosciences, 2016)
Phenology, seed morphology, seed viability and germination behabiour of some wetland plants in control at moist filter paper in petridishes was carried out in wetland plants-Aeschynemone asper L. (Fabaceae); Eragrostis unioloides (Retz.) Nees exsteudel (Poaceae); Hygrophila auriculata (K. Schum) Heine (Acanthaceae); Pesicaria barbatum (L.) Hara (Polygonaceae); and Rumex dentatus L. (Polygonaceae) were studied at Biratnagar. Number of seeds per gram ranged between161-12722. Viable seeds of A. asper (98%) and P. barbatum (55%) had no germination but E. unioloides had cent percent germination; H. auriculata, and Rumex dentatus showed 96% germination. A.asper and E. unioloides germinated in early rainy; spent vegetative phase up to August- September; and completed flowering, fruiting and seed maturation before winter.